2019
DOI: 10.1063/1.5116533
|View full text |Cite
|
Sign up to set email alerts
|

Parametric effects in circuit quantum electrodynamics

Abstract: We review recent advances in the research on quantum parametric phenomena in superconducting circuits with Josephson junctions. We discuss physical processes in parametrically driven tunable cavity and outline theoretical foundations for their description. Amplification and frequency conversion are discussed in detail for degenerate and non-degenerate parametric resonance, including quantum noise squeezing and photon entanglement. Experimental advances in this area played decisive role in successful developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…The circuit QED with "artificial atoms" (qubits) was the subject of studies [338][339][340][341][342][343][344][345][346][347][348][349][350]. The most recent review on parametric effects in circuit QED can be found in [351].…”
Section: Circuit Dcementioning
confidence: 99%
“…The circuit QED with "artificial atoms" (qubits) was the subject of studies [338][339][340][341][342][343][344][345][346][347][348][349][350]. The most recent review on parametric effects in circuit QED can be found in [351].…”
Section: Circuit Dcementioning
confidence: 99%
“…The success of these experiments was related to the possibility of achieving the effective velocity of the boundary up to 25% of the light velocity in vacuum (although the analogy with the motion of real boundaries is not perfect). Many theoretical papers suggesting further improvements of the experimental schemes were published during the past decade: see more references in [87][88][89][90].…”
Section: Dynamical Casimir Effectmentioning
confidence: 99%
“…Such processes were observed already in the very first experiment 5 and also play a pivotal role for the Josephson laser 3 where, however, they mix with fundamental (p = 1) resonances for higher modes ω p = pω 0 of the cavity. Equivalent processes in ac-driven Josephson devices 47 have very recently been observed for p = 3 downconversion. [48][49][50] In the classical description these processes, which based on a quantum picture may be called p-photon creation processes, materialize as (higher-order) parametric resonances in the equations-of-motion.…”
Section: Higher-order Resonancesmentioning
confidence: 99%